Integrating Qur’anic and Prophetic Principles in Educational Quality Assurance - Imro’atus Solikah; Agus Zaenul Fitri; As’aril Muhajir (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates how Islamic principles derived from the Qur’an and Hadith such as ihsan (excellence), amanah (trust), accountability, and continuous improvement inform and enrich the concept of educational quality assurance. It aims to examine the relevance of these values to modern quality assurance frameworks and their practical implementation at SMAI Sunan Gunung Jati Tulungagung. Employing a qualitative descriptive approach, the research utilized document analysis, literature review, and field observation. The findings reveal that Islamic values are deeply embedded in the school’s strategic planning, quality programs, performance evaluation, and work culture, providing both ethical guidance and managerial structure. This integration enhances the effectiveness and integrity of the institution’s quality assurance efforts. The study concludes that harmonizing Islamic teachings with modern quality assurance systems can contribute to a more holistic and value-driven model of educational excellence.